Development of chitosan-gelatin nanofibers with cellulose nanocrystals for skin protection applications - Ribeiro, Ana S. (2021)
In this work, natural-based and biodegradable nanofibers were produced by electrospinning for drug delivery and wound dressing applications, using gelatin (Gel), chitosan (CS), cellulose nanocrystals (CNC) and natural propolis extract. The polymeric formulations and electrospinning parameters were optimized, resulting in the development of Gel/CS nanofibers with mean diameters of 97 nm. CNC were successfully introduced into the optimized Gel/CS solution and the viscosity and conductivity values were recorded. The developed nanofibers were characterized using FESEM, ATR-FTIR, TGA and WCA. The incorporation of different CNC concentrations improved the solutions’ electrospinnability and the membranes’ physical integrity. Defect-free and uniform Gel/CS/CNC nanofibers were observed by FESEM images, and the fibers’ diameters slight increased. The hydrophilic character was maintained after the CNC incorporation. Finally, Gel/CS/CNC/Propolis nanofibers demonstrated antibacterial activity against both Gram-negative (E. coli) and Gram-positive (S. aureus) bacteria